2022
DOI: 10.3390/v14061151
|View full text |Cite
|
Sign up to set email alerts
|

HIV Antiretroviral Medication Neuropenetrance and Neurocognitive Outcomes in HIV+ Adults: A Review of the Literature Examining the Central Nervous System Penetration Effectiveness Score

Abstract: This literature review summarizes the existing research examining the CNS penetration effectiveness (CPE) score and neurocognitive outcomes (i.e., neuropsychological assessment and neurocognitive screening) in HIV+ individuals. Despite the effectiveness of Combined Antiretroviral Therapy (CART) in reducing mortality and morbidity in HIV and controlling viral replication, HIV often persists in the Central Nervous System (CNS), and rates of neurocognitive impairment remain higher than predicted in the post-CART … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 70 publications
(128 reference statements)
0
13
0
Order By: Relevance
“…25 Despite this possibility, a recent study concluded that ART with higher CPE is associated with modest improvement in global neurocognitive functioning, with less improvement noted in specific cognitive domains such as attention, working memory and learning. 26 This could explain why significant improvements were noted in the IHDS and processing speed and not in BNCE with its strong emphasis on higher orders of cognitive function. Overall, it has been found that higher CPE regimens are slightly more likely to preserve or improve cognitive function than regimens with lower CPE scores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Despite this possibility, a recent study concluded that ART with higher CPE is associated with modest improvement in global neurocognitive functioning, with less improvement noted in specific cognitive domains such as attention, working memory and learning. 26 This could explain why significant improvements were noted in the IHDS and processing speed and not in BNCE with its strong emphasis on higher orders of cognitive function. Overall, it has been found that higher CPE regimens are slightly more likely to preserve or improve cognitive function than regimens with lower CPE scores.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, it has been found that higher CPE regimens are slightly more likely to preserve or improve cognitive function than regimens with lower CPE scores. 26 Research comparing dolutegravir-based regimens with other regimens of lower total CPE value would be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…ART use was self-reported and confirmed via review of medical regimen records if available. Distribution of ART drugs into the central nervous system was estimated using the central nervous system penetration effectiveness (CPE) value (Arentoft et al, 2022; Letendre et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…This agrees with the study by Arentoft et al that antiretrovirals with higher penetration score significantly increase recovery rate in susceptible individuals. 49 Besides the CPE scores, previous drug history, resistance patterns and tolerability were considered in determining an alternative therapy.…”
Section: T a B L Ementioning
confidence: 99%